SOUTH JAKARTA YOUTH’S URBAN LIFESTYLE AS A FORM OF SELF-EXISTENCE ON TIKTOK - Risqi Inayah Dwijayanti; Dina Sudarmika; Nurul aini (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
TikTok has become a primary space for urban teenagers in South Jakarta to express themselves and shape their social identity amidst the pressures of modern lifestyle. Its function has gone beyond mere entertainment, serving as a platform for existence and the pursuit of social recognition. Teenagers face various social pressures that push them to follow trends and present themselves visually through content related to fashion, social activities, and participation in viral phenomena. This study aims to understand how the urban youth lifestyle is reflected in TikTok content, and how social demands and the desire for existence shape their digital behavior. Using a qualitative method with an interpretive paradigm and a case study strategy, data were collected through content observation, in-depth interviews, and documentation. The theoretical framework applied is hedonism, which explains how individuals seek pleasure and recognition from their social environment. The findings reveal that TikTok plays a significant role in influencing the lifestyle and identity formation of teenagers, where digital existence becomes an essential part of their self-actualization process.